Evidence for a Rad18-Independent Frameshift Mutagenesis Pathway in Human Cell-Free Extracts - Janel-Bintz, Régine; Wagner, Jérôme; Haracska, Lajos; Mah-Becherel, Marcia Chia Miao; Bichara, Marc; Fuchs, Robert P.; Cordonnier, Agnès M. (PLOS ONE, 2012)
Bypass of replication blocks by specialized DNA polymerases is crucial for cell survival but may promote mutagenesis and genome instability. To gain insight into mutagenic sub-pathways that coexist in mammalian cells, we examined N-2-acetylaminofluorene (AAF)-induced frameshift mutagenesis by means of SV40-based shuttle vectors containing a single adduct. We found that in mammalian cells, as previously observed in E. coli, modification of the third guanine of two target sequences, 5'-GGG-3' (3G) and 5'-GGCGCC-3' (NarI site), induces –1 and –2 frameshift mutations, respectively. Using an in vitro assay for translesion synthesis, we investigated the biochemical control of these events. We showed that Pol eta, but neither Pol iota nor Pol zeta, plays a major role in the frameshift bypass of the AAF adduct located in the 3G sequence. By complementing PCNA-depleted extracts with either a wild-type or a non-ubiquitinatable form of PCNA, we found that this Pol eta-mediated pathway requires Rad18 and ubiquitination of PCNA. In contrast, when the AAF adduct is located within the NarI site, TLS is only partially dependent upon Pol eta and Rad18, unravelling the existence of alternative pathways that concurrently bypass this lesion.